Peningkatan Keterampilan Berbicara Siswa Dengan Implementasi Model Debat Tematik - Uditia Hoerotun Nisa; Yayan Carlian (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2020)
The learning process cannot be separated from speaking activities, in other words speaking is an important part of everyday life. The purpose of learning to speak is so that students can use the language orally properly and correctly. However, in reality, speaking skills in learning activities are still not optimal, and they are not given enough attention. The purpose of this study was to determine speaking skills before applying the debate learning model. As well as knowing the speaking skills of students after using the debate model of class V students of MI Naelushibyan, Bandung Regency. This is also due to speaking skills that do not use the right model. The research model used was Classroom Action Research (PTK). This research was conducted at MI Naelushibyan, Bandung Regency. Speaking skills after using the debate model were included in the sufficient category with an average score of 54.5 in the I action cycle I, in the I action II cycle the students got an average score of 63. While in the second cycle students got an average score of 68 in action I and 87% of action II. The conclusion of this study is the application of the debate learning model can improve students' speaking skills in thematic learning